Contextual Criminalization in European Criminal Law: From Security Paradigm to Value-Oriented Justice - Туляков, Вячеслав Олексійович; Туляков, В. О.; Tuliakov, Viacheslav O. (Elsevier, 2025)
Traditional theory of criminalization, grounded in liberal principles of harm prevention and minimal state intervention, provides clear and objective criteria for determining the grounds of criminal liability. These criteria ensure predictability and legal certainty by dividing conduct into criminal and non-criminal on the basis of stable features, thus creating a solid foundation for law enforcement. However, the modern world generates new challenges-transnational crimes, cybercrime, terrorism, and environmental offenses-which, due to their complex social, technical, and cultural nature, do not always fit within classical frameworks. This calls for more flexible and context-sensitive approaches that preserve legal certainty but are capable of adapting to diverse situations. In this context, the concept of contextual criminalization, developed by Tuliakov and Savinova (2024), gains particular significance as an innovative approach to reshaping the architecture of criminal law. Contextual criminalization emphasizes the criminogenic role of the unified set of offense elements, highlighting that certain acts become criminal not merely because of their intrinsic nature but due to specific circumstances, purposes, or contexts that give them particular social harmfulness, especially when they infringe upon individual rights and fundamental values. Традиційна теорія криміналізації, що ґрунтується на ліберальних принципах запобігання шкоді та мінімального втручання держави, забезпечує чіткі та об'єктивні критерії для визначення підстав кримінальної відповідальності. Ці критерії забезпечують передбачуваність та правову визначеність, поділяючи поведінку на кримінальну та некримінальну на основі стабільних ознак, створюючи таким чином міцну основу для правоохоронної діяльності. Однак сучасний світ породжує нові виклики – транснаціональні злочини, кіберзлочинність, тероризм та екологічні правопорушення, – які через свою складну соціальну, технічну та культурну природу не завжди вписуються в класичні рамки. Це вимагає більш гнучких та контекстно-чутливих підходів, які зберігають правову визначеність, але здатні адаптуватися до різних ситуацій. У цьому контексті концепція контекстуальної криміналізації, розроблена Туляковим та Савіновою (2024), набуває особливого значення як інноваційний підхід до перетворення архітектури кримінального права. Контекстуальна криміналізація підкреслює криміногенну роль єдиного набору елементів правопорушення, підкреслюючи, що певні діяння стають злочинними не лише через свою внутрішню природу, але й через конкретні обставини, цілі чи контексти, які надають їм особливої ​​соціальної шкідливості, особливо коли вони порушують права особистості та фундаментальні цінності.
Tuliakov V. O. Contextual Criminalization in European Criminal Law: From Security Paradigm to Value-Oriented Justice / V. O. Tuliakov // SSRN : website. - 4 p. - Access mode: https://ssrn.com/abstract=5542758 ; http://dx.doi.org/10.2139/ssrn.5542758 ; https://hdl.handle.net/11300/30686. - Publication date : 29.09.2025
Keywords: Criminalization; Criminal Policy; Crime; EU Values; ECHR; Human Rights Approach; Victim's Rights; Transnational; Криміналізація; кримінальна політика; злочинність; цінності ЄС; ЄСПЛ; підхід до прав людини; права жертв; транснаціональне право